Microbiological study of the invasive oyster Saccostrea cucullata: seasonal variation of total and thermotolerant coliforms in the Cananéia Estuarine Complex during the 2018-2019 season - Barbieri , Edison; de Souza Araújo , Ana Lúzia; Oliveira Rezende , Karina Fernandes; Vasquez, Felipe (O Mundo da Saúde, 2024)
In the estuarine lagoon complex of Cananéia, state of São Paulo, southeast region, there is fresh consumption of the invasive oyster Saccostrea cucullata, mainly in summer, high season. It is a filter-feeding mollusk that presents a risk of serious pathologies of the gastrointestinal system due to the risk of storing microbiological agents that affect humans. The lack of monitoring, good manufacturing practices, water quality and control measures to ensure the safety and quality of oyster consumption is necessary for the prevention of pathogens in public health. This study carried out microbiological analyzes of oyster samples, focusing on mesophilic bacteria, psychrotrophic bacteria and fungi/yeasts. Furthermore, seasonal concentrations of total and thermotolerant coliforms were investigated in oyster samples collected over a year. Counts of mesophilic bacteria in oysters ranged from 1.45±0.22 to 3.32±0.28 log CFU g–1, with average values of 2.24±0.86 log CFU g–1. For psychrotrophic bacteria in oyster samples it ranged between 1.34±0.29 and 3.12±0.45 log CFU g–1. The data revealed that fungal and yeast counts ranged from 2.65±0.23 to 3.57±0.22 log CFU g–1. The maximum S. aureus count was 1.24 log CFU g–1, and 83.5% of the samples tested negative for this microorganism. No presence of Salmonella spp. was detected in the analyzed data. These results provide important insights into seasonal variation and microbiological counts in oyster samples, highlighting the relevance of microbiological monitoring and control in marine food products.